A method for preparing high-performance rubber material for automobile tires
By adding specific modified components to the rubber material for automobile tires, the problem of insufficient performance of rubber material in the prior art is solved, and a high-performance rubber material with excellent tensile performance, hardness and wear resistance is prepared.
Patent Information
- Application Number
- CN202411675718.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The prior art has no obvious effect in improving the wear resistance, hardness and tensile properties of rubber materials for automobile tires, and it is difficult to meet the high requirements of the automobile industry for high performance rubber materials.
By adding antioxidant RD to the rubber matrix to the rubber matrix, the amount and treatment method of each component are optimized to prepare high-performance rubber materials.
The produced rubber material not only has excellent tensile properties and high hardness, but also shows good wear resistance, which can better meet the needs of automotive tires.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a method for preparing a high-performance rubber material for automobile tires. Background Art
[0002] Natural rubber is made from latex produced by rubber trees through curing and drying processes. Rubber materials have long molecular chains and can form an elastic network structure through cross-linking reactions. When subjected to external forces, they can produce large deformations and have the ability to return to their original state when the external force is removed. This performance brings a wide range of use value to rubber materials, and they have been widely used in the fields of automobiles, aerospace, sealing products, shock-absorbing and damping components, etc.
[0003] In the automotive industry, tires are the most common rubber products. Nowadays, as people's requirements for high speed, safety, energy saving and other aspects of automobiles are increasing, the industry has higher and higher requirements for the performance of rubber materials used in tires. For example, the wear resistance, hardness, tensile properties of rubber materials not only affect the economic efficiency of automobile use, but also affect the safety of automobiles. In particular, the wear resistance of tires is one of the most critical performance parameters during their use and has become a research focus in related fields.
[0004] The patent with application number CN201711053468.7 provides a rubber composition for highly wear-resistant automobile tire treads, and its raw material formula includes the following components in parts by weight: base rubber: 70 to 80 parts of styrene-butadiene rubber, 20 to 30 parts of natural rubber; functional filler: 30 to 50 parts of modified fumed silica, 40 to 60 parts of carbon black; reinforcing component: 10 to 20 parts of Kevlar fiber; tackifying resin: 10 to 20 parts of epoxy resin; vulcanization component: 5 to 10 parts of vulcanizer, 2 to 5 parts of vulcanization accelerator. The patent with application number CN201911132576.2 provides a highly elastic and wear-resistant rubber composition for automobile tires, characterized in that it includes the following components by weight: 45-65 parts of natural rubber, 25-30 parts of butadiene rubber, 30-40 parts of butadiene rubber, 10-20 parts of isoprene rubber, 5-10 parts of vulcanizing agent, 25-35 parts of white carbon black, 10-20 parts of silicon dioxide, 2-5 parts of carbon fiber, 2-5 parts of graphite fiber, and 5-10 parts of chitosan. Although the above-mentioned prior art can improve the performance of the material to a certain extent, the effect is not obvious. Summary of the invention
[0005] The technical problem to be solved by the present invention is: in view of the shortcomings of the prior art, a method for preparing a high-performance rubber material for automobile tires is provided. The preparation method is simple to operate and requires mild conditions. The prepared rubber material not only has excellent tensile properties, but also has high hardness and good wear resistance.
[0006] In order to solve the above technical problems, the technical solution of the present invention is:
[0007] A method for preparing a high-performance rubber material for automobile tires comprises the following steps:
[0008] (1) activating the carboxylated graphene oxide, and then grafting and modifying the graphene oxide with an antioxidant RD to obtain antioxidant RD grafted graphene oxide;
[0009] (2) adding the pretreated titanium oxide to a mixed solution of anhydrous ethanol, isopropanol, ammonia water and distilled water, stirring once, adding ethyl orthosilicate, stirring twice, adding a modifier, stirring three times, and finally drying to obtain a modified titanium oxide / silicon oxide nanomaterial;
[0010] (3) The carbon black is hydroxylated and then dispersed in anhydrous ethanol to obtain a hydroxylated carbon black dispersion, and vinyl trimethoxysilane and γ-methacryloxypropyl trimethoxysilane are used as silanization agents to prepare a silane hydrolyzate; the silane hydrolyzate and the hydroxylated carbon black dispersion are mixed and reacted, and after the reaction is completed, the mixture is filtered, and the precipitate is washed to obtain a modified carbon black;
[0011] (4) Natural rubber, cis-1,4-butadiene rubber and styrene-butadiene rubber are added to an internal mixer for primary mixing. After heating, stearic acid, zinc oxide, antioxidant RD grafted modified graphene oxide, modified titanium oxide / silicon oxide powder, modified carbon black and plasticizer are added for secondary mixing. After cooling, vulcanization accelerator and sulfur are added. The rubber compound is thinned and then triangularly packaged to form a sheet. The rubber compound is left for 10-20 hours and finally vulcanized on a flat vulcanizer to obtain a high-performance rubber material for automobile tires.
[0012] Preferably, in step (1), the preparation process of the activated carboxylated graphene oxide is: dispersing the carboxylated graphene oxide in anhydrous ethanol to obtain a carboxylated graphene oxide dispersion, adjusting the pH of the carboxylated graphene oxide dispersion to 3-4, reacting in a water bath at 55-65° C. for 5-7 hours, then filtering, washing the precipitate and drying to obtain activated carboxylated graphene oxide.
[0013] Preferably, in step (1), the specific process of the grafting modification is: mixing the antioxidant RD and the silane coupling agent KH560 in a molar ratio of 1:1, reflux reaction at 135-145°C for 2-4h to obtain a grafting solution; mixing the activated carboxylated graphene oxide and the grafting solution in a mass ratio of 1:(1-3), heating to 75-85°C for reaction for 5-7h, and after the reaction is completed, cooling the reaction solution to room temperature and filtering, washing the filtered precipitate and drying to obtain the antioxidant RD grafted modified graphene oxide.
[0014] Preferably, in step (2), the specific process of the titanium oxide pretreatment is: ultrasonically treating titanium oxide, octadecyltrichlorosilane and ethanol at 200-500W for 1-2h, and then drying to obtain pretreated titanium oxide; the mass ratio of the titanium oxide to octadecyltrichlorosilane is 1:(0.2-2.0).
[0015] Preferably, in step (2), the concentration of the ammonia water is 20-30wt%, and the mass ratio of the pretreated titanium oxide, anhydrous ethanol, isopropanol, ammonia water, distilled water, and tetraethyl orthosilicate is 1:(:40-50):(40-50):(10-20):80:(0.002-0.005);
[0016] and / or the modifier is a mixture of KH570, KH550 and phenyltrimethoxysilane, wherein the mass ratio of KH570, KH550, phenyltrimethoxysilane and tetraethyl orthosilicate is 1:1:1:(2-3);
[0017] and / or the temperature of the first stirring is room temperature and the time is 20-30 min; and / or the temperature of the second stirring is 30-40° C. and the time is 1-2 h; and / or the temperature of the third stirring is 65-75° C. and the time is 2-3 h.
[0018] Preferably, in step (3), the specific process of the hydroxylation treatment is: carbon black and hydrogen peroxide with a concentration of 25-30wt% are mixed in a ratio of (2-5) g: 200 ml, and ultrasonically treated at 200-500W for 20-30min to obtain a carbon black dispersion, the carbon black dispersion is heated to 55-65°C, and stirred at a speed of 500-600rpm for reaction for 20-30h, and filtered after completion. The filtered precipitate is washed and dried to obtain hydroxylated carbon black.
[0019] Preferably, in step (3), the preparation process of the silane hydrolyzate is: vinyl trimethoxysilane and γ-methacryloxypropyl trimethoxysilane are mixed in a mass ratio of 1:1 and added to a mixed solution of anhydrous ethanol and deionized water, and the mass ratio of vinyl trimethoxysilane, anhydrous ethanol and deionized water is controlled to be (1-5): (2-8): (50-100), and then acetic acid is added to adjust the pH to 3-5, and the mixture is treated at a stirring speed of 1000-2000 rpm for 1-2 hours to obtain a silane hydrolyzate.
[0020] Preferably, in step (3), the concentration of the hydroxylated carbon black dispersion is 0.05-0.1 g / ml; and / or when the silane hydrolyzate is mixed with the hydroxylated carbon black dispersion, the mass ratio of vinyltrimethoxysilane to hydroxylated carbon black is controlled to be (0.01-0.02):1; and / or the temperature of the mixing reaction is 85-90°C, the stirring speed is 800-1000 rpm, and the time is 3-5h.
[0021] Preferably, in step (4), the temperature during the first mixing is 50-60°C, the speed of the internal mixer is 45-50 rpm, and the time is 2-5 min; and / or the temperature of the second mixing is 100-110°C, the speed of the internal mixer is 45-50 rpm, and the time is 1-2 min; and / or the temperature of adding the vulcanization accelerator and sulfur is 60-75°C; and / or the vulcanization temperature is 140-180°C, the vulcanization pressure is 8-15 MPa, and the vulcanization time is 20-30 min.
[0022] Preferably, in step (4), the amounts of the components used in parts by weight are: 50-90 parts of natural rubber, 25-55 parts of butadiene rubber, 30-50 parts of styrene-butadiene rubber, 0.3-0.5 parts of stearic acid, 1-2 parts of zinc oxide, 5-8 parts of antioxidant RD grafted modified graphene oxide, 5-10 parts of modified titanium oxide / silicon oxide powder, 30-50 parts of modified carbon black, 1-2 parts of plasticizer, 0.5-1 parts of vulcanization accelerator, and 1-3 parts of sulfur.
[0023] Preferably, in step (4), the plasticizer is plasticizer DCHP, and the vulcanization accelerator is one of vulcanization accelerator M, vulcanization accelerator DM, and vulcanization accelerator CZ.
[0024] Due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0025] 1. The present invention provides a method for preparing a high-performance rubber material for automobile tires. The material prepared by the method includes natural rubber, butadiene rubber, styrene-butadiene rubber, stearic acid, zinc oxide, antioxidant RD grafted modified graphene oxide, modified titanium oxide / silicon oxide nanomaterials, modified carbon black, plasticizer, vulcanization accelerator, and sulfur. By optimizing the amount of each component, the prepared material has not only high hardness, but also good tensile properties and excellent wear resistance.
[0026] 2. The present invention adds a certain amount of antioxidant RD grafted modified graphene oxide to the rubber matrix. Graphene oxide has a high specific surface area and can provide more effective contact points, thereby improving the strength of the material. In addition, graphene oxide has high rigidity and excellent thermal stability, making the rubber composite material perform better in friction and wear. In order to improve the compatibility of graphene oxide with the rubber matrix, the present invention first activates the carboxylated graphene oxide, and then grafts the antioxidant RD on the surface of the carboxylated graphene oxide under certain conditions for modification. The obtained antioxidant RD grafted modified graphene oxide can be stably dispersed in the rubber matrix, thereby enhancing its heat aging resistance and oxygen aging resistance. Even under high temperature and abrasive environments, the matrix can maintain stable friction and wear performance.
[0027] 3. The present invention adds a certain amount of modified titanium oxide / silicon oxide nanomaterials to the rubber matrix. Titanium oxide has excellent mechanical strength and rigidity, and can effectively enhance the mechanical properties of the rubber matrix. Silicon oxide has high hardness and wear resistance, and can form a protective layer on the surface of the rubber material to reduce friction and wear. This protective effect enables the rubber to better resist the erosion of the external environment during use and prolong its service life. In order to improve the dispersibility of titanium oxide and silicon oxide in the rubber matrix, the present invention first prepares titanium oxide / silicon oxide nanomaterials with a core-shell structure, and then uses a variety of modifiers to modify its surface. The obtained modified titanium oxide / silicon oxide nanomaterials have good compatibility with the rubber matrix, which can not only improve the strength of the rubber matrix, but also improve its tensile strength, so that the rubber is not easy to break when subjected to force. In addition, the interface bonding of silicon oxide and titanium oxide also helps to improve the bonding strength of the material and enhance the interaction between rubber and filler. This enhanced interfacial bonding force can effectively transmit stress, thereby further improving the overall performance of the material.
[0028] 4. In order to improve the compatibility of carbon black and rubber matrix, the present invention first performs hydroxylation treatment on carbon black, and then uses vinyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane for graft silanization treatment; after modification, the interface interaction between carbon black and rubber matrix is improved, thereby producing better surface bonding, improving the dispersibility of modified carbon black in rubber matrix, and thus better improving the performance of rubber matrix. DETAILED DESCRIPTION
[0029] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
[0030] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.
[0031] In the following examples and comparative examples, carboxylated graphene oxide: thickness 0.8-1.2 nm, sheet diameter 0.5-5 μm, purity 99.8%, purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; titanium oxide: rutile type, average particle size 20-40 nm, specific surface area 77.37 m 2 / g, purity of 99%, purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; carbon black: carbon black N375, purchased from Shanghai Cabot Chemical Co., Ltd.; natural rubber: grade SCR-5, density 0.913g / cm 3 , purchased from Hainan Agricultural Reclamation Investment Holding Group Co., Ltd.; butyl rubber: brand 9000, purchased from Zhejiang Chuanhua Synthetic Materials Co., Ltd.; styrene butadiene rubber: solution styrene butadiene rubber, brand KC3737T, a product of Eni Versalis, Italy.
[0032] Unless otherwise specified, other raw materials are commercially available, and the conditions are conventional conditions in the art unless otherwise specified. Example 1
[0033] A method for preparing a high-performance rubber material for automobile tires comprises the following steps:
[0034] (1) Dispersing 1 g of carboxylated graphene oxide in 500 ml of anhydrous ethanol to obtain a carboxylated graphene oxide dispersion, adjusting the pH of the carboxylated graphene oxide dispersion to 3, reacting in a water bath at 60° C. for 5 h, then filtering, washing the precipitate and drying to obtain activated carboxylated graphene oxide; mixing antioxidant RD and silane coupling agent KH560 in a molar ratio of 1:1, reflux reacting at 140° C. for 3 h to obtain a grafting solution; mixing activated carboxylated graphene oxide and the grafting solution in a mass ratio of 1:1, heating to 80° C. for reaction for 5 h, cooling the reaction solution to room temperature after the reaction is completed, filtering, washing the precipitate after filtration and drying to obtain antioxidant RD grafted modified graphene oxide;
[0035] (2) 1 g of titanium oxide, 0.5 g of octadecyltrichlorosilane and 100 ml of ethanol were ultrasonically treated at 500 W for 1 h, and then dried to obtain pretreated titanium oxide; 1 g of pretreated titanium oxide was added to a mixed solution consisting of 45 g of anhydrous ethanol, 45 g of isopropanol, 12 g of 25 wt% ammonia water and 80 g of distilled water, stirred at room temperature for 20 min, 0.003 g of ethyl orthosilicate was added, stirred at 35 ° C for 1 h, 0.003 g of modifier (KH570, KH550, phenyltrimethoxysilane were mixed in a mass ratio of 1:1:1) was added, stirred at 70 ° C for 2 h, and finally dried to obtain modified titanium oxide / silicon oxide nanomaterials;
[0036] (3) Mix carbon black and 25wt% hydrogen peroxide in a ratio of 2g:200ml, and ultrasonically treat at 300W for 20min to obtain a carbon black dispersion. Heat the carbon black dispersion to 60°C, stir and react at a speed of 500rpm for 20-30h, filter after completion, wash the precipitate after filtration and dry to obtain hydroxylated carbon black; disperse 2g of the above hydroxylated carbon black in 25ml of anhydrous ethanol to obtain a hydroxylated carbon black dispersion; mix 0.03g of vinyltrimethoxysilane, 0.03g of γ-methacryloxypropyltrimethoxysilane, 0.05g of anhydrous ethanol and 1g of deionized water, then add acetic acid to adjust the pH to 4, and treat at a stirring speed of 1000rpm for 1h to obtain a silane hydrolyzate; add the silane hydrolyzate to the above hydroxylated carbon black dispersion, and react at 85°C and 900rpm for 3h;
[0037] (4) In parts by weight, 65 parts of natural rubber, 50 parts of cis-1,4-dibutyl rubber and 30 parts of styrene-butadiene rubber were added to an internal mixer and mixed at 55°C and 45 rpm for 5 min. After the temperature was raised to 100°C, 0.3 parts of stearic acid, 1 part of zinc oxide, 5 parts of antioxidant RD grafted modified graphene oxide, 5 parts of modified titanium oxide / silicon oxide nanomaterials, 30 parts of modified carbon black and 2 parts of plasticizer (plasticizer DCHP) were added and mixed at a speed of 45 rpm for 2 min. After the temperature was lowered to 60°C, 0.5 parts of vulcanization accelerator (vulcanization accelerator DM) and 1 part of sulfur were added. The rubber compound was thinned and then triangularly packaged 5 times to form a sheet. The rubber compound was left to stand for 20 h. Finally, the rubber compound was vulcanized on a flat vulcanizer at 150°C and 9 MPa for 20 min to obtain a high-performance rubber material for automobile tires. Example 2
[0038] A method for preparing a high-performance rubber material for automobile tires comprises the following steps:
[0039] (1) Dispersing 1 g of carboxylated graphene oxide in 500 ml of anhydrous ethanol to obtain a carboxylated graphene oxide dispersion, adjusting the pH of the carboxylated graphene oxide dispersion to 4, reacting in a water bath at 60° C. for 6 h, then filtering, washing the precipitate and drying to obtain activated carboxylated graphene oxide; mixing antioxidant RD and silane coupling agent KH560 in a molar ratio of 1:1, reflux reacting at 140° C. for 3 h to obtain a grafting solution; mixing activated carboxylated graphene oxide and the grafting solution in a mass ratio of 1:2, heating to 80° C. for 6 h, cooling the reaction solution to room temperature after the reaction, filtering, washing the precipitate after filtration and drying to obtain antioxidant RD grafted modified graphene oxide;
[0040] (2) 1 g of titanium oxide, 1 g of octadecyltrichlorosilane and 100 ml of ethanol were ultrasonically treated at 300 W for 2 h, and then dried to obtain pretreated titanium oxide; 1 g of pretreated titanium oxide was added to a mixed solution consisting of 50 g of anhydrous ethanol, 50 g of isopropanol, 15 g of 25 wt% ammonia water and 80 g of distilled water, stirred at room temperature for 20-30 min, 0.002-0.005 g of ethyl orthosilicate was added, stirred at 30-40 ° C for 1-2 h, 0.003 g of a modifier (KH570, KH550, phenyltrimethoxysilane were mixed in a mass ratio of 1:1:1) was added, stirred at 70 ° C for 2 h, and finally dried to obtain modified titanium oxide / silicon oxide powder;
[0041] (3) Mix carbon black and 25wt% hydrogen peroxide in a ratio of 4g:200ml, and ultrasonically treat at 400W for 20min to obtain a carbon black dispersion. Heat the carbon black dispersion to 60°C, stir and react at 600rpm for 24h, filter after completion, wash the filtered precipitate and dry to obtain hydroxylated carbon black. Disperse 2g of the above hydroxylated carbon black in 25ml of anhydrous ethanol to obtain a hydroxylated carbon black dispersion. Mix 0.03g of vinyltrimethoxysilane, 0.03g of γ-methacryloxypropyltrimethoxysilane, 0.05g of anhydrous ethanol and 1g of deionized water, then add acetic acid to adjust the pH to 4, and treat at a stirring speed of 1000rpm for 2h to obtain a silane hydrolyzate. Add the silane hydrolyzate to the above hydroxylated carbon black dispersion and react at 85°C and 900rpm for 4h.
[0042] (4) In parts by weight, 70 parts of natural rubber, 45 parts of cis-1,4-dibutyl rubber and 40 parts of styrene-butadiene rubber were added to an internal mixer and mixed at 55°C and 50 rpm for 4 min. After the temperature was raised to 100°C, 0.4 parts of stearic acid, 2 parts of zinc oxide, 6 parts of antioxidant RD grafted modified graphene oxide, 5 parts of modified titanium oxide / silicon oxide nanomaterials, 35 parts of modified carbon black and 1.5 parts of plasticizer (plasticizer DCHP) were added and mixed at a speed of 50 rpm for 2 min. After the temperature was lowered to 65°C, 1 part of vulcanization accelerator (vulcanization accelerator DM) and 2 parts of sulfur were added. The rubber compound was thinned and then triangularly packaged 5 times to form a sheet. The rubber compound was left to stand for 20 h. Finally, the rubber compound was vulcanized on a flat vulcanizer at 155°C and 10 MPa for 20 min to obtain a high-performance rubber material for automobile tires. Example 3
[0043] A method for preparing a high-performance rubber material for automobile tires comprises the following steps:
[0044] (1) Dispersing 1 g of carboxylated graphene oxide in 500 ml of anhydrous ethanol to obtain a carboxylated graphene oxide dispersion, adjusting the pH of the carboxylated graphene oxide dispersion to 3, reacting in a water bath at 60° C. for 6 h, then filtering, washing the precipitate and drying to obtain activated carboxylated graphene oxide; mixing antioxidant RD and silane coupling agent KH560 in a molar ratio of 1:1, reflux reacting at 140° C. for 3 h to obtain a grafting solution; mixing activated carboxylated graphene oxide and the grafting solution in a mass ratio of 1:1, heating to 80° C. for 6 h, cooling the reaction solution to room temperature after the reaction, filtering, washing the precipitate after filtration and drying to obtain antioxidant RD grafted modified graphene oxide;
[0045] (2) 1 g of titanium oxide, 1 g of octadecyltrichlorosilane and 100 ml of ethanol were ultrasonically treated at 400 W for 2 h, and then dried to obtain pretreated titanium oxide; 1 g of pretreated titanium oxide was added to a mixed solution consisting of 40 g of anhydrous ethanol, 50 g of isopropanol, 12 g of 25 wt% ammonia water and 80 g of distilled water, stirred at room temperature for 30 min, 0.004 g of ethyl orthosilicate was added, stirred at 35 ° C for 2 h, 0.003 g of modifier (KH570, KH550, phenyltrimethoxysilane were mixed in a mass ratio of 1:1:1) was added, stirred at 70 ° C for 2 h, and finally dried to obtain modified titanium oxide / silicon oxide powder;
[0046] (3) Mix carbon black and 28wt% hydrogen peroxide in a ratio of 3g:200ml, and ultrasonically treat at 400W for 20min to obtain a carbon black dispersion. Heat the carbon black dispersion to 60°C, stir and react at 600rpm for 24h, filter after completion, wash the filtered precipitate and dry to obtain hydroxylated carbon black. Disperse 2g of the above hydroxylated carbon black in 25ml of anhydrous ethanol to obtain a hydroxylated carbon black dispersion. Mix 0.03g of vinyltrimethoxysilane, 0.03g of γ-methacryloxypropyltrimethoxysilane, 0.06g of anhydrous ethanol and 1g of deionized water, then add acetic acid to adjust the pH to 4, and treat at a stirring speed of 1000rpm for 2h to obtain a silane hydrolyzate. Add the silane hydrolyzate to the above hydroxylated carbon black dispersion and react at 85°C and 800rpm for 4h.
[0047] (4) In parts by weight, 60 parts of natural rubber, 52 parts of butadiene rubber and 40 parts of styrene butadiene rubber were added to an internal mixer and mixed at 50°C and 45 rpm for 5 min. After the temperature was raised to 100°C, 0.4 parts of stearic acid, 2 parts of zinc oxide, 7 parts of antioxidant RD grafted modified graphene oxide, 8 parts of modified titanium oxide / silicon oxide nanomaterials, 40 parts of modified carbon black and 1 part of plasticizer (plasticizer DCHP) were added and mixed at a speed of 45 rpm for 1 min. After the temperature was lowered to 60°C, 1 part of vulcanization accelerator (vulcanization accelerator DM) and 2 parts of sulfur were added. The rubber compound was thinned and then triangularly packaged 5 times to form a sheet. The rubber compound was left to stand for 20 h. Finally, the rubber compound was vulcanized on a flat vulcanizer at 150°C and 11 MPa for 20 min to obtain a high-performance rubber material for automobile tires. Example 4
[0048] A method for preparing a high-performance rubber material for automobile tires comprises the following steps:
[0049] (1) Dispersing 1 g of carboxylated graphene oxide in 500 ml of anhydrous ethanol to obtain a carboxylated graphene oxide dispersion, adjusting the pH of the carboxylated graphene oxide dispersion to 4, reacting in a water bath at 60° C. for 6 h, then filtering, washing the precipitate and drying to obtain activated carboxylated graphene oxide; mixing antioxidant RD and silane coupling agent KH560 in a molar ratio of 1:1, reflux reacting at 140° C. for 4 h to obtain a grafting solution; mixing activated carboxylated graphene oxide and the grafting solution in a mass ratio of 1:3, heating to 80° C. for 6 h, cooling the reaction solution to room temperature after the reaction, filtering, washing the precipitate after filtration and drying to obtain antioxidant RD grafted modified graphene oxide;
[0050] (2) 1 g of titanium oxide, 2 g of octadecyltrichlorosilane and 100 ml of ethanol were ultrasonically treated at 400 W for 2 h, and then dried to obtain pretreated titanium oxide; 1 g of pretreated titanium oxide was added to a mixed solution consisting of 50 g of anhydrous ethanol, 45 g of isopropanol, 12 g of 25 wt% ammonia water and 80 g of distilled water, stirred at room temperature for 30 min, 0.005 g of ethyl orthosilicate was added, stirred at 35 ° C for 2 h, 0.003 g of modifier (KH570, KH550, phenyltrimethoxysilane were mixed in a mass ratio of 1:1:1) was added, stirred at 70 ° C for 3 h, and finally dried to obtain modified titanium oxide / silicon oxide powder;
[0051] (3) Mix carbon black and 25wt% hydrogen peroxide in a ratio of 5g:200ml, and ultrasonically treat at 500W for 20min to obtain a carbon black dispersion. Heat the carbon black dispersion to 60°C, stir and react at 600rpm for 24h, filter after completion, wash the filtered precipitate and dry to obtain hydroxylated carbon black. Disperse 2g of the above hydroxylated carbon black in 25ml of anhydrous ethanol to obtain a hydroxylated carbon black dispersion. Mix 0.03g of vinyltrimethoxysilane, 0.03g of γ-methacryloxypropyltrimethoxysilane, 0.07g of anhydrous ethanol and 1g of deionized water, then add acetic acid to adjust the pH to 4, and treat at a stirring speed of 1000rpm for 2h to obtain a silane hydrolyzate. Add the silane hydrolyzate to the above hydroxylated carbon black dispersion and react at 85°C and 800rpm for 5h.
[0052] (4) In parts by weight, 85 parts of natural rubber, 50 parts of cis-1,4-butadiene rubber and 45 parts of styrene-butadiene rubber were added to an internal mixer and mixed at 50°C and 45 rpm for 5 min. After the temperature was raised to 100°C, 0.4 parts of stearic acid, 1 part of zinc oxide, 5 parts of antioxidant RD grafted modified graphene oxide, 5 parts of modified titanium oxide / silicon oxide nanomaterials, 30 parts of modified carbon black and 1.5 parts of plasticizer (plasticizer DCHP) were added and mixed at a speed of 45 rpm for 2 min. After the temperature was lowered to 60°C, 1 part of vulcanization accelerator (vulcanization accelerator DM) and 2 parts of sulfur were added. The rubber compound was thinned and then triangularly packaged 5 times to form a sheet. The rubber compound was left to stand for 20 h. Finally, the rubber compound was vulcanized on a flat vulcanizer at 145°C and 10 MPa for 20 min to obtain a high-performance rubber material for automobile tires.
[0053] In order to verify the performance of the high-performance rubber material for automobile tires prepared by the present invention, the following is a detailed description with reference to Example 4 and combined with a comparative example.
[0054] Comparative Example 1
[0055] Compared with Example 4, the difference is that antioxidant RD, silane coupling agent KH560 and carboxylated graphene oxide are used to replace the antioxidant RD grafted modified graphene oxide in Example 4, the dosage ratio of antioxidant RD, silane coupling agent KH560 and carboxylated graphene oxide is the same as that in Example 4, and other conditions are the same as those in Example 4.
[0056] Comparative Example 2
[0057] Compared with Example 4, the difference is that in step (2), no pre-treated titanium oxide is added, and the other conditions are the same as those in Example 4.
[0058] Comparative Example 3
[0059] Compared with Example 4, the difference is that in step (2), the modifier is KH570, and the other conditions are the same as those in Example 4.
[0060] Comparative Example 4
[0061] Compared with Example 4, the difference is that in step (2), the modifier is KH550, and the other conditions are the same as those in Example 4.
[0062] Comparative Example 5
[0063] Compared with Example 4, the difference is that in step (2), the modifier is phenyltrimethoxysilane, and the other conditions are the same as those in Example 4.
[0064] Comparative Example 6
[0065] Compared with Example 4, the difference is that in step (2), the modifier is a mixture of KH570 and KH550 in a mass ratio of 1:1, and the other conditions are the same as those in Example 4.
[0066] Comparative Example 7
[0067] Compared with Example 4, the difference is that in step (2), the modifier is a mixture of KH550 and phenyltrimethoxysilane in a mass ratio of 1:1:1, and the other conditions are the same as those in Example 4.
[0068] Comparative Example 8
[0069] Compared with Example 4, the difference is that in step (2), the modifier is a mixture of KH5570 and phenyltrimethoxysilane in a mass ratio of 1:1:1, and the other conditions are the same as those in Example 4.
[0070] Comparative Example 9
[0071] Compared with Example 4, the difference is that in step (2), no modifier is added, and the other conditions are the same as those in Example 4.
[0072] Comparative Example 10
[0073] Compared with Example 4, the difference is that in step (3), an equal amount of vinyltrimethoxysilane is used to replace γ-methacryloxypropyltrimethoxysilane, and other conditions are the same as those in Example 4.
[0074] Comparative Example 11
[0075] Compared with Example 4, the difference is that in step (3), an equal amount of γ-methacryloxypropyltrimethoxysilane is used to replace vinyltrimethoxysilane, and other conditions are the same as those in Example 4.
[0076] Comparative Example 12
[0077] Compared with Example 4, the difference is that an equal amount of carbon black is used to replace the modified carbon black in Example 4, and other conditions are the same as Example 4.
[0078] Comparative Example 13
[0079] Compared with Example 4, the difference is that an equal amount of modified carbon black is used to replace the modified titanium oxide / silicon oxide nanomaterial in Example 4, and other conditions are the same as those in Example 4.
[0080] Comparative Example 14
[0081] Compared with Example 4, the difference is that an equal amount of modified carbon black is used to replace the antioxidant RD grafted modified graphene oxide in Example 4, and other conditions are the same as Example 4.
[0082] Comparative Example 15
[0083] Compared with Example 4, the difference is that an equal amount of modified carbon black is used to replace the antioxidant RD grafted modified graphene oxide and modified titanium oxide / silicon oxide nanomaterials in Example 4, and other conditions are the same as Example 4.
[0084] The performance tests of the high-performance rubber materials for automobile tires prepared in the above embodiments and comparative examples are as follows:
[0085] 1. Tensile performance test:
[0086] The samples prepared by the pneumatic cutting machine were dumbbell-shaped specimens with a length of 80 mm and a working area width of 6 mm. The tensile test conditions were set at a tensile rate of 500 mm / min, and the tensile strength and elongation at break of the rubber were measured.
[0087] 2. Shore A hardness test:
[0088] According to the national standard GB / T531.1-2008, the test is carried out using a hardness tester at room temperature.
[0089] 3. Wear resistance:
[0090] The rubber materials prepared in the test examples and comparative examples according to GB / T1689-2014 were tested at 30°C, 50°C, and 70°C with a mileage of 1.61 km using a RW-7813B high temperature AKRON abrasion tester under the experimental conditions of a standard load of 26.7 N and a standard angle of 15°. Three samples were tested for each sample, and the average value was taken as the final measurement result.
[0091] The test results are shown in Table 1.
[0092] Table 1
[0093]
[0094] According to the test results in Table 1, the analysis is as follows:
[0095] Compared with the comparative example, the embodiment of the present invention uses antioxidant RD grafted modified carboxylated graphene oxide, modified carbon black and modified titanium oxide / silicon oxide nanomaterials to modify the rubber matrix, and the obtained rubber material has not only good mechanical properties, but also good wear resistance.
[0096] In Comparative Example 1, the antioxidant RD and the activated carboxylated graphene oxide were directly physically mixed and added to the rubber material. The free antioxidant RD was easily accumulated and agglomerated, resulting in a decrease in various properties of the rubber material.
[0097] In Comparative Example 2, titanium oxide is not pretreated, which will affect the uniformity of silicon oxide coating on its surface, so that the obtained modified titanium oxide / silicon oxide nanomaterial added to the rubber material cannot improve the performance of the rubber material well.
[0098] In Comparative Examples 3 to 9, when preparing modified titanium oxide / silicon oxide nanomaterials, a single type of modifier or no modifier is used, and the prepared nanomaterials are added to the rubber matrix material. The performance of the material is reduced compared with that of Example 4, which is mainly related to the dispersion of the nanomaterial in the rubber matrix material. Compared with Comparative Examples 3-9, Example 4 uses a compound of KH550, phenyltrimethoxysilane, and KH570 as a modifier, thereby introducing a variety of functional groups on the surface of the titanium oxide / silicon oxide material, so that the modified nanomaterial can be better combined with the matrix material, thereby improving the dispersion of the material.
[0099] Compared with Example 4, the performance of the materials in Comparative Examples 10-12 is slightly reduced. In Example 4, vinyl trimethoxy silane and γ-methacryloxypropyl trimethoxy silane are used to jointly modify carbon black, thereby better improving the dispersibility of carbon black in the matrix material.
[0100] Compared with Example 4, Comparative Examples 13-15 do not add modified titanium oxide / silicon oxide nanomaterials or antioxidant RD grafted modified graphene oxide or do not add antioxidant RD grafted modified graphene oxide and modified titanium oxide / silicon oxide nanomaterials at the same time, and the performance of the material is greatly reduced. Because the antioxidant RD grafted modified graphene oxide added in Example 4 has a good reinforcing ability in the rubber matrix, the grafting modification of carboxylated graphene oxide by antioxidant RD not only avoids the migration of antioxidant RD and causes the thermal oxidation aging performance of the material to decrease, but also improves the compatibility of carboxylated graphene oxide with the rubber matrix, thereby better improving the performance of the material. Moreover, titanium oxide and silicon oxide both have good mechanical strength. Example 4 uses silicon oxide to coat titanium oxide, which improves the dispersibility of titanium oxide and titanium oxide. The surface is modified by three types of modifiers, which improves the bonding performance of titanium oxide / silicon oxide nanomaterials with the rubber matrix, so that titanium oxide / silicon oxide nanomaterials can be evenly dispersed in the rubber, providing additional support and reinforcement.
[0101] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.
Claims
1. A method for preparing a high-performance rubber material for automobile tires, characterized in that: The following steps are involved: (1) Antioxidant RD and silane coupling agent KH560 are mixed in a molar ratio of 1:1, and refluxed at 135-145°C for 2-4 hours to obtain a grafting solution; activated carboxylated graphene oxide and grafting solution are mixed in a mass ratio of 1:(1-3), heated to 75-85°C for 5-7 hours, and after the reaction is completed, the reaction solution is cooled to room temperature and filtered, the filtered precipitate is washed and dried to obtain antioxidant RD grafted modified graphene oxide; (2) After pretreatment, titanium oxide is added to a mixed solution of anhydrous ethanol, isopropanol, ammonia water and distilled water, stirred once, tetraethyl orthosilicate is added, stirred twice, a modifier is added, stirred three times, and finally dried to obtain a modified titanium oxide / silicon oxide nanomaterial; the modifier is a mixture of KH570, KH550 and phenyltrimethoxysilane, and the mass ratio of KH570, KH550, phenyltrimethoxysilane and tetraethyl orthosilicate is 1:1:1:(2-3); (3) After carbon black is subjected to hydroxylation treatment, it is dispersed in anhydrous ethanol to obtain a hydroxylated carbon black dispersion, and vinyl trimethoxysilane and γ-methacryloxypropyl trimethoxysilane are mixed in a mass ratio of 1:1 as a silanization agent to prepare a silane hydrolyzate; the silane hydrolyzate and the hydroxylated carbon black dispersion are mixed and reacted to obtain modified carbon black; the mass ratio of vinyl trimethoxysilane to hydroxylated carbon black is (0.01-0.02): 1; (4) Natural rubber, cis-1,4-butadiene rubber and styrene-butadiene rubber are added to an internal mixer for primary mixing. After heating, stearic acid, zinc oxide, antioxidant RD grafted modified graphene oxide, modified titanium oxide / silicon oxide nanomaterials, modified carbon black and plasticizer are added for secondary mixing. After cooling, vulcanization accelerator and sulfur are added. The rubber compound is thinly passed and then triangularly packaged to produce sheets. The rubber compound is left for 10-20 hours and finally vulcanized on a flat vulcanizer to obtain automobile tires. High-performance rubber material; the amounts of the components in parts by weight are: 50-90 parts of natural rubber, 25-55 parts of butadiene rubber, 30-50 parts of styrene-butadiene rubber, 0.3-0.5 parts of stearic acid, 1-2 parts of zinc oxide, 5-8 parts of antioxidant RD grafted modified graphene oxide, 5-10 parts of modified titanium oxide / silicon oxide nanomaterials, 30-50 parts of modified carbon black, 1-2 parts of plasticizer, 0.5-1 parts of vulcanization accelerator, and 1-3 parts of sulfur.
2. The method for preparing a high-performance rubber material for automobile tires according to claim 1, characterized in that: In step (1), the preparation process of activated carboxylated graphene oxide is as follows: dispersing carboxylated graphene oxide in anhydrous ethanol to obtain a carboxylated graphene oxide dispersion, adjusting the pH of the carboxylated graphene oxide dispersion to 3-4, reacting in a water bath at 55-65° C. for 5-7 hours, then filtering, washing the precipitate and drying to obtain activated carboxylated graphene oxide.
3. The method for preparing a high-performance rubber material for automobile tires according to claim 1, characterized in that: In step (2), the specific process of the titanium oxide pretreatment is: ultrasonically treating titanium oxide, octadecyltrichlorosilane and ethanol at 200-500W for 1-2h, and then drying to obtain pretreated titanium oxide; the mass ratio of titanium oxide to octadecyltrichlorosilane is controlled to be 1: (0.2-2.0).
4. The method for preparing a high-performance rubber material for automobile tires according to claim 3, characterized in that: In step (2), the concentration of the ammonia water is 20-30wt%, and the mass ratio of the pretreated titanium oxide, anhydrous ethanol, isopropanol, ammonia water, distilled water, and tetraethyl orthosilicate is 1: (40-50): (40-50): (10-20): 80: (0.002-0.005); and / or the temperature of the first stirring is room temperature and the time is 20-30 min; and / or the temperature of the second stirring is 30-40° C. and the time is 1-2 h; and / or the temperature of the third stirring is 65-75° C. and the time is 2-3 h.
5. The method for preparing a high-performance rubber material for automobile tires according to claim 1, characterized in that: In step (3), the hydroxylation process is specifically as follows: carbon black and 25-30wt% hydrogen peroxide are mixed in a ratio of (2-5) g: 200 ml, and ultrasonically treated at 200-500 W for 20-30 min to obtain a carbon black dispersion, the carbon black dispersion is heated to 55-65° C., and stirred at a speed of 500-600 rpm for reaction for 20-30 h. After completion, the dispersion is filtered, the filtered precipitate is washed, and then dried to obtain hydroxylated carbon black.
6. The method for preparing a high-performance rubber material for automobile tires according to claim 1, characterized in that: In step (3), the preparation process of the silane hydrolyzate is as follows: vinyl trimethoxysilane and γ-methacryloxypropyl trimethoxysilane are mixed and added to a mixed solution of anhydrous ethanol and deionized water, and the mass ratio of vinyl trimethoxysilane, anhydrous ethanol and deionized water is controlled to be (1-5): (2-8): (50-100), and then acetic acid is added to adjust the pH of the solution to 3-5, and the solution is treated at a stirring speed of 1000-2000 rpm for 1-2 hours to obtain a silane hydrolyzate.
7. The method for preparing a high-performance rubber material for automobile tires according to claim 1, characterized in that: In step (3), the concentration of the hydroxylated carbon black dispersion is 0.05-0.1 g / ml; and / or the temperature of the mixing reaction is 85-90° C., the stirring speed is 800-1000 rpm, and the time is 3-5 hours.
8. The method for preparing a high-performance rubber material for automobile tires according to claim 1, characterized in that: In step (4), the temperature of the first mixing is 50-60°C, the speed of the internal mixer is 45-50rpm, and the time is 2-5min; and / or the temperature of the second mixing is 100-110°C, the speed of the internal mixer is 45-50rpm, and the time is 1-2min; and / or the temperature of adding the vulcanization accelerator and sulfur is 60-75°C; and / or the vulcanization temperature is 140-180°C, the vulcanization pressure is 8-15MPa, and the vulcanization time is 20-30min.
9. The method for preparing a high-performance rubber material for automobile tires according to claim 1, characterized in that: In step (4), the plasticizer is plasticizer DCHP, and the vulcanization accelerator is one of vulcanization accelerator M, vulcanization accelerator DM, and vulcanization accelerator CZ.
Citation Information
Patent Citations
A rubber composition for high wear-resistant automotive tire tread
CN107746487B
High-elasticity wear-resistant rubber composition for automobile tire
CN110818962A
Super-wear-resistant modified natural rubber / butadiene rubber blended rubber composite material and preparation method thereof
CN118725421A
Rubber with high adhesion and preparation method thereof
CN118813168A